Synbiotics supplement is effective for Melasma improvement - Piyanat Piyavatin (2022)
Background: Melasma is a disorder of melanogenesis among humans causing localized, chronic acquired hypermelanosis of the skin requiring a combination of treatments. Related studies have shown probiotics contribute distinct advantages for skin disorders possibly including melasma because of its anti-inflammatory activities, anti-oxidation properties, ultraviolet protection, and tyrosinase activity inhibition. Aims: The study aimed to investigate the effects of synbiotics supplement on improving melasma (evaluated from mMASI score). Methods: This research comprised an experimental study employing a prospective, double-blind, randomized controlled trial among 57 Thai participants divided in 2 groups (29 for the experimental and 28 for the placebo groups). The participants were aged 30-50 years old, had Fitzpatrick skin type III–VI, with facial melasma on both sides of the face and attending Mae Fah Luang University Hospital, Bangkok from January-December 2019. Participants were randomly treated with oral synbiotics or placebo, 1 sachet daily for 12 weeks. Melasma severity and skin health were evaluated at 4 visits for each participant (baseline, weeks 4, 8, and 12, respectively). Results: Severity of melasma scored by mMASI of the synbiotics group was 7.54 ± 0.79, 7.36 ± 0.80, 7.16 ± 0.73, and 6.98 ± 0.72 at baseline, weeks 4, 8, and 12, respectively, and 7.51 ± 0.86, 7.52 ± 0.88, 7.54 ± 0.86, and 7.54 ± 0.89 at baseline, weeks 4, 8, and 12, respectively, in the placebo group. Comparing between two groups at week 12, melasma score in the synbiotics supplement group was significantly lower than that in the placebo group (P =.008). Conclusion: Oral synbiotics supplementation for 12 weeks improved the severity of melasma score.